2008
DOI: 10.1103/physrevlett.100.103905
|View full text |Cite
|
Sign up to set email alerts
|

Static Envelope Patterns in Composite Resonances Generated by Level Crossing in Optical Toroidal Microcavities

Abstract: We study level crossing in the optical whispering-gallery (WG) modes by using toroidal microcavities. Experimentally, we image the stationary envelope patterns of the composite optical modes that arise when WG modes of different wavelengths coincide in frequency. Numerically, we calculate crossings of levels that correspond with the observed degenerate modes, where our method takes into account the not perfectly transverse nature of their field polarizations. In addition, we analyze anticrossing with a large a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
70
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 33 publications
3
70
0
Order By: Relevance
“…The difference in FSR between different mode families is on the order of 1 GHz, resulting from different spatial mode structure within the toroid. Note that some mode positions are strongly affected by mode crossings with other families [20], leading to a locally increased dispersion. The evolution of the FSR of the mode with the highest optical Q-factor in this cavity is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in FSR between different mode families is on the order of 1 GHz, resulting from different spatial mode structure within the toroid. Note that some mode positions are strongly affected by mode crossings with other families [20], leading to a locally increased dispersion. The evolution of the FSR of the mode with the highest optical Q-factor in this cavity is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In such resonators, the transverse (radial-polar) order of one mode can compensate for the frequency difference originating from the non-similar longitudinal (azimuthal) order of the other. This provides a pair of modes with different azimuthal wavevectors, but nearby frequencies, as experimentally observed via the resulting stationary interference pattern [5,6]. The energy flow in Brillouin anti-Stokes cooling [2] that is analyzed here, is opposite in respect to the Stokes excitation process [7][8][9].…”
mentioning
confidence: 83%
“…This is because two optical resonances that have almost the same optical frequency but different propagation constants are needed in order to conseerve both the energy and momentum which are given to light by the acoustical phonon. One type of cavity that allows such optical-resonance pairs is whispering-gallery mode resonators [5,6]. In such resonators, the transverse (radial-polar) order of one mode can compensate for the frequency difference originating from the non-similar longitudinal (azimuthal) order of the other.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We show that a proper shaping of the resonator results in a significant reduction of the SAW WGM volume that further increases the process efficiency. To achieve phase matching between optical and acoustic waves we propose to use the interference patterns generated at the surface of the WGM resonator [18,19]. We have found that such patterns can be created even by WGMs having different polarizations, which significantly simplifies the control of the acousto-optical processes in resonators with birefringent host material.…”
mentioning
confidence: 99%